2004
DOI: 10.1590/s0101-81752004000400011
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitat selection and co-occurrence of Pachistopelma rufonigrum Pocock (Araneae, Theraphosidae) and Nothroctenus fuxico sp. nov. (Araneae, Ctenidae) in tank bromeliads from Serra de Itabaiana, Sergipe, Brazil

Abstract: Microhabitat selection and co-occurrence of Pachistopelma rufonigrum Pocock (Theraphosidae) and Nothroctenus fuxico sp. nov. (Ctenidae), in tank bromeliads were investigated. Thermal conditions, inside and outside the plants, were measured in order to verify if the temperature of the water that accumulates inside the plant affects the behavior of these species. Measurements of foliar parameters were taken in order to evaluate if and how plant structure affects spider abundance and microhabitat selection. Appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0
6

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 13 publications
2
22
0
6
Order By: Relevance
“…Our results on the wandering spiders agree with studies that show species-specific habitat preferences within different taxa of animals; e.g., assemblages of frogs, lizards, and spiders (Uetz 1977;Reagan 1992;Dias & Brescovit 2004;Menin et al 2005;D'Cruze & Stafford 2006;Williams et al 2006;Entling et al 2007;Torres-Sá nchez & Gasnier 2010).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results on the wandering spiders agree with studies that show species-specific habitat preferences within different taxa of animals; e.g., assemblages of frogs, lizards, and spiders (Uetz 1977;Reagan 1992;Dias & Brescovit 2004;Menin et al 2005;D'Cruze & Stafford 2006;Williams et al 2006;Entling et al 2007;Torres-Sá nchez & Gasnier 2010).…”
Section: Discussionsupporting
confidence: 88%
“…Frequently, these large spiders occur sympatrically with the New World endemic family Trechaleidae (superfamily Lycosoidea: Silva Davila 2003) that contains species of similar size to the Ctenidae (Carico 1993). Although some studies have focused on various aspects of selected tropical wandering spider taxa (Van Berkum 1982;Barth et al 1988;Carico et al 1985;Schmitt et al 1990;Carico 1993;Hö fer et al 1994;Gasnier & Hö fer 2001;Steyn et al 2002;Dias & Brescovit 2004;Torres-Sá nchez & Gasnier 2010), no studies on community patterns within assemblages of similarly sized sympatric species belonging to different families are yet available. Consequently, our goal was to make an ecological analysis of an assemblage of large wandering spider species.…”
mentioning
confidence: 99%
“…Dentre os trabalhos existentes, alguns mostram associação entre o ecótopo e a utilização de microhabitat pela araneofauna (COSTA; PERÉZ-MILES, 1992;STRADLING, 1994;DIAS;BRESCOVIT, 2003;RHEIMS;. Outros procuram relacionar as aranhas com plantas hospedeiras (DIAS; , sendo mais voltados a estudos realizados em florestas tropicais úmidas e secas, com análise da fauna associada às copas de árvores.…”
Section: Introductionunclassified
“…We observed that the ground temperature on the inselberg at Monte Verde reached 50Њ C during the day (15:00 h), while among the bromeliad leaves and in the phytotelmata the temperature was 27Њ C and 22Њ C, respectively. Hence, the phytotelmata appear to function as a thermoregulatory mechanism for the bromeliads and indirectly provide a suitable microclimate for the spiders (see also Dias & Brescovit 2004).…”
Section: Discussionmentioning
confidence: 99%